Compensated Changes in Quantities and Qualities Consumed - Houthakker, H. S. (Review of Economic Studies, 1952)
Compensated Changes in Quantities and Qualities Consumed Get access H. S. Houthakker H. S. Houthakker Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 3, 1952, Pages 155–164, https://doi.org/10.2307/2296018 Published: 01 January 1952